2021
DOI: 10.1155/2021/5515383
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Survival of Preformed Zirconia Crowns in Children Treated under General Anesthesia

Abstract: Aim. This study aimed to retrospectively evaluate the success of zirconia crowns placed in the anterior teeth of children and evaluate the impact of pulp therapy of the tooth on the rate of failure. Materials and Methods. A total of 70 anterior teeth of 20 children aged between 3 and 5 years who had undergone the placement of zirconia crowns under general anesthesia were followed up for 24 months. Kaplan–Meier Survival curves were plotted for the estimation of two-year survival time. The outcomes for teeth tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…It can be thought that crown retention may be less than the group without pulp treatment, since teeth requiring pulp treatment have more material loss due to deep caries. As a matter of fact, in a previous study 27 , they revealed that crown loss was higher in teeth that had pulpal treatment. However, there was no difference in our study; It can be attributed to increasing the retention of the crowns by compensating the tissue losses in pulpal treated teeth with filling materials with high adhesion strength before the ZCs is placed.…”
Section: Discussionmentioning
confidence: 89%
“…It can be thought that crown retention may be less than the group without pulp treatment, since teeth requiring pulp treatment have more material loss due to deep caries. As a matter of fact, in a previous study 27 , they revealed that crown loss was higher in teeth that had pulpal treatment. However, there was no difference in our study; It can be attributed to increasing the retention of the crowns by compensating the tissue losses in pulpal treated teeth with filling materials with high adhesion strength before the ZCs is placed.…”
Section: Discussionmentioning
confidence: 89%
“…Most, if not all available studies on crowns for primary teeth have recruited children aged < 10 years [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. However, the age distribution of the included participants is not commonly reported.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 13 RCTs and 5 clinical studies (prospective and retrospective) were included in this systematic review [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Figure 1 presents the PRISMA flow diagram illustrating the study selection process.…”
Section: Selection Of Studies and Risk Of Bias Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations